(3GdHjGf Gdhaj HbQGAI MaU Yf YGUe Gdchajs - (3CMeO Hf CMeO Hf YeQ GdfThis; (3WGgQ Hf jMji Hf CHj GdNjQ SGde, CHh GdWjH GdYeQGfj,J (B587 (3g` s ((3CMeO Hf eMeO Hf CMeO YHOGdeJYGd s)
(3ChdgG (B:s
(3CeG HYO adeG cGf Chdi eG JUQa Edjg Gdgee hGdCacGQ cdGe Gddg SHMGfg hJYGdi GdhGMO GdbgGQ s
(3BNQgG (B:s
(3hdc GdMeO jG ef JJe HfYeJg GdUGdMGJ hZad Yf PcQg GdZGadhf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B83s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B223 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B39s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B267) s
Keywords: (3GdbQGAGJ hGdJLhjOs